2021
DOI: 10.1088/1755-1315/756/1/012043
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of total phenolic content and antioxidant activity in medicinal Aroid, Alocasia longiloba Miq.

Abstract: Alocasia longiloba Miq belongs to Araceae family, believed to have the medicinal potential. However, the scientific evidences on this plant were limited. Therefore, this study aimed to evaluate the total phenolic content (TPC) and antioxidant activity of the different extracts (methanol, ethyl acetate and hexane) of A. longiloba leaf blades. The TPC was investigated by Folin-Ciocalteu method and antioxidant activity was determined by DPPH scavenging assay. The results showed ethyl acetate extract had the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Reactive oxygen species or oxidants play a crucial role in damaging cells, tissues, and biological systems of plants, their extracted products, and so forth. The quantity of these reactive oxygen species can be controlled or minimized by the action of certain types of antioxidants present in various parts of the plants (Nur‐Izzati et al, 2021). All the methanolic and ethanolic extracts (flower, leaf, and stem) of T. linearis exhibited a significant amount of antioxidant potential.…”
Section: Resultsmentioning
confidence: 99%
“…Reactive oxygen species or oxidants play a crucial role in damaging cells, tissues, and biological systems of plants, their extracted products, and so forth. The quantity of these reactive oxygen species can be controlled or minimized by the action of certain types of antioxidants present in various parts of the plants (Nur‐Izzati et al, 2021). All the methanolic and ethanolic extracts (flower, leaf, and stem) of T. linearis exhibited a significant amount of antioxidant potential.…”
Section: Resultsmentioning
confidence: 99%
“…The results regarding TFC of whole fruit and pulp are in good agreement with that reported by Elazzouzi et al ( 2002 ) and Lamia et al ( 2018 ) who observed that TFC detected in Opuntia pulp was 22.47 ± 2.1 mg RE/100 g DW. These variations in TFC might be due to the solubility capacity of matrix components and the polarity of a hydroethanolic mixture (Luque‐Rodriguez et al, 2007 ; Nur‐Izzati et al, 2021 ; Shi et al, 2003 ; Toure et al, 2015 ). Previously, reported findings have also suggested that solvent polarity maximizes the extraction yields of flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…Medicinal plants or herbs have long been utilized in folk medicines to treat several ailments in several parts of the world ( Okoye et al, 2014 , Oladeji, 2016 , Ferid et al, 2020 , Nur-Izzati et al, 2021 ). Ifeoma and Oluwakanyinsol (2013) , reported that approximately one-fourth of pharmaceutically prescribed in the world contains at least one plant-based constituent.…”
Section: Introductionmentioning
confidence: 99%